Cycle Sustainability - Pirlone, Francesca; Candia, Selena (TeMA - Journal of Land Use, Mobility and Environment, 2015)
<!–[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><p class="ABSTRACT" style="mso-element: frame; mso-element-frame-hspace: 0cm; mso-element-wrap: auto; mso-element-anchor-vertical: margin; mso-element-anchor-horizontal: column; mso-element-left: left; mso-element-top: 0cm; mso-height-rule: exactly;">One of the main problems that affects modern cities is connected to transport/mobility. Urban transport is currently based on car use; the transition to the use of more sustainable means of transport is happening slowly. Bicycles used as main way of transport, combined with walking, it’s a successful solution for many towns to really bring traffic and congestion down. For their high density and their short time travels, towns are the best places (in comparison to long time travels as merchandise transport) to reduce the green houses gasses emitted promoting walking, cycling and public transport. For this reason the European Union is directly founding different projects that boost urban cycling. Many examples presented in this paper where collected by an European project. This project sectioned best practices and excellences in cycling as the so called cycle cities: Amsterdam, Copenhagen, Seville,…cities that have recognized the importance of cycling as a solution to traffic congestion. But how is it possible to transfer these experiences to others realities? <p class="ABSTRACT" style="mso-element: frame; mso-element-frame-hspace: 0cm; mso-element-wrap: auto; mso-element-anchor-vertical: margin; mso-element-anchor-horizontal: column; mso-element-left: left; mso-element-top: 0cm; mso-height-rule: exactly;">The scope of this article is to show the sustainability of cycling according to socio-economic (social and economic sustainability) and environmental terms (environmental sustainability). <p class="ABSTRACT" style="mso-element: frame; mso-element-frame-hspace: 0cm; mso-element-wrap: auto; mso-element-anchor-vertical: margin; mso-element-anchor-horizontal: column; mso-element-left: left; mso-element-top: 0cm; mso-height-rule: exactly;">For this reason is proposed a CBA (Cost and Benefits Analysis) methodology specific to evidence the advantages of investments in cycling made by public authorities or private companies both, to promote and realize ecological infrastructures. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> 1024x768 <![endif]–> One of the main problems that affects modern cities is connected to transport/mobility. Urban transport is currently based on car use; the transition to the use of more sustainable means of transport is happening slowly. Bicycles used as main way of transport, combined with walking, it’s a successful solution for many towns to really bring traffic and congestion down. For their high density and their short time travels, towns are the best places (in comparison to long time travels as merchandise transport) to reduce the green houses gasses emitted promoting walking, cycling and public transport. For this reason the European Union is directly founding different projects that boost urban cycling. Many examples presented in this paper where collected by an European project. This project sectioned best practices and excellences in cycling as the so called cycle cities: Amsterdam, Copenhagen, Seville,…cities that have recognized the importance of cycling as a solution to traffic congestion. But how is it possible to transfer these experiences to others realities? The scope of this article is to show the sustainability of cycling according to socio-economic (social and economic sustainability) and environmental terms (environmental sustainability). For this reason is proposed a CBA (Cost and Benefits Analysis) methodology specific to evidence the advantages of investments in cycling made by public authorities or private companies both, to promote and realize ecological infrastructures. <!–[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>